"Wówczas tatuś rozpoczął opowieść": próba rekonstrukcji oralnych początków wybranych utworów "dziecięcych" J.R.R. Tolkiena - Neubauer, Łukasz (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The article seeks to examine the indisputably oral origins of Tolkien’s works for children, in particular his two short books Roverandom (1998) and Farmer Giles of Ham (1949), which were originally conceived in the mid- and late-1920s. Each of them appears to have developed from a story that was first told for the amusement of his sons. The former began as a consolation tale after the then-five-yearold Michael had lost his favourite lead dog figurine during the summer holidays of 1925. The latter is said to have developed from an unspecified “local family game” whose roots may lie in the Tolkiens’ interest in local toponymy. Despite the differences in both style and structure, the two books share a number of features, especially with regard to their oral origins and the subsequently added layers of sophisticated philological jokes.
Keywords: J.R.R. Tolkien; oralność; Rudy Dżil i jego pies; Łazikanty